Short-term pilot feasibility study of a nurse-led intervention to improve blood pressure control after stroke in Nigeria (2017)
Background: Given the paucity of neurologists in Sub-Saharan Africa (SSA), task-shifting post-stroke care to nurses could be a viable avenue for enhancing post-stroke outcomes. This pilot study assessed the feasibility and short-term impact of a nurse-led intervention to manage blood pressure (BP) control in recent stroke survivors in Nigeria. Methods: A randomized pilot trial allocated patients within one month of an index stroke from two participating hospitals in Nigeria to either nurse-led group clinic or standard care for 14 days. Key study endpoints were successful execution of the protocol, subject retention, and short-term BP effects. Results: There were no significant differences between the intervention (n = 17) and control (n = 18) groups at baseline. At the post-intervention clinic, patient retention rate was 100%. In the intervention group, both the systolic and diastolic BPs measured at home were lower than the clinic BPs post-interven tion (127 ± 12.88/78.13 ± 19.26 mmHg versus 137.50 ± 23.05/84.06 ± 9.67 mmHg; p = 0.05). However, there was no significant change in clinic blood pressure (BP) recordings in both the intervention and control groups. Conclusion: It is possible to initiate a nurse-led group clinic intervention to address BP management among stroke survivors in SSA with good early retention of participants. A larger and longer-term trial is being planned.